Mitochondrial adaptor TRAK2 activates and functionally links opposing kinesin and dynein motors - Adam R. Fenton (Nature Portfolio, 2021)
Mitochondrial transport toward both the plus- and minus-ends of microtubules is mediated by motor proteins linked to mitochondria by TRAK adaptor proteins. Here the authors investigate the role of TRAK2 as a bidirectional motor adaptor, and propose a model where TRAK2 coordinates the activities of opposing kinesin-1 and cytoplasmic dynein motors as a single interdependent motor complex.